Hyperpolarized Carbon-13 Magnetic Resonance Imaging: Technical Considerations and Clinical Applications - Lai, Ying-Chieh; Hsieh, Ching-Yi; Juan, Yu-Hsiang; Lu, Kuan-Ying; Lee, Hsien-Ju; Ng, Shu-Hang; Wan, Yung-Liang; Lin, Gigin (Korean journal of radiology, 2024)
Hyperpolarized (HP) carbon-13 ( C) MRI represents an innovative approach for noninvasive, real-time assessment of dynamic metabolic flux, with potential integration into routine clinical MRI. The use of [1- C]pyruvate as a probe and its conversion to [1- C]lactate constitute an extensively explored metabolic pathway. This review comprehensively outlines the establishment of HP C-MRI, covering multidisciplinary team collaboration, hardware prerequisites, probe preparation, hyperpolarization techniques, imaging acquisition, and data analysis. This article discusses the clinical applications of HP C-MRI across various anatomical domains, including the brain, heart, skeletal muscle, breast, liver, kidney, pancreas, and prostate. Each section highlights the specific applications and findings pertinent to these regions, emphasizing the potential versatility of HP C-MRI in diverse clinical contexts. This review serves as a comprehensive update, bridging technical aspects with clinical applications and offering insights into the ongoing advancements in HP C-MRI.